Rekontruksi Lingkungan Kerja, Karakteristik Individu dan Kinerja Karyawan Di Bank Syariah Indonesia Berdasarkan Budaya Kerja “Akhlak” (Studi Literatur) - Agustina, Wirda Eka; Widyaningsih, Bekti; Rahmat Ika, Arivatu Nimati (FEB Universitas Maritim Semarang, 2024)
The aim of this research is to determine the influence of the work environment, individual characteristics and employee performance at Bank Syariah Indonesia. This research uses a qualitative approach using literature study and technical content analysis. In the work environment at Bank Syariah Indonesia there is a huge support for the creation of a company's activity processes. With a good working environment, good and pleasant working conditions will be created, this can provide employee morale. According to (Rahmawanti et al., 2014). a work environment that is always around workers who are able to influence them in carrying out the tasks they have been burdened with. Meanwhile, individual characteristics are that each person must have different views, goals, abilities and needs from each other. These differences will bring habits into the world of work, which will cause self-satisfaction and cause differences between each other even though they work in the same place. An employee's performance is the result of a person's work during the period of work, for example standards, targets or target criteria that have been determined in advance and have been mutually agreed upon.